Chromatographic profile of fatty acids and sugars in cupcakes functionalized with an extract rich in rosmarinic acid - Caleja, Cristina (2018)
Currently, the food industry is interested in replacing artificial additives by natural ingredients. Some plant extracts have emerged as possible alternatives to artificial preservatives, namely antioxidants. In fact, dairy, meat and bakery products have been developed, incorporating extracts of aromatic plants, spices or fruits, which have antioxidant properties. In this work, the preserving effectiveness of an extract rich in rosmarinic acid was tested in cupcakes and compared to an artificial additive (potassium sorbate, E202). The extract was obtained from Melissa officinalis L. (lemon balm) by applying an ultrasound technique using a mixture of ethanol/water as the extraction solvent. After confirming its antioxidant properties (free radical scavenging effect EC50 = 79 ± 2 μg/mL; reducing power EC50 = 49 ± 1 μg/mL), antimicrobial (against 8 bacteria and 8 food contaminating fungi), and absence of toxicity (in cell lines), it was incorporated in cupcakes, and analysed immediately after incorporation and after 3 and 5 days of storage at room temperature and protected from light. All samples were analysed chromatographically in terms of fatty acids (GC-FID) and free sugars (HPLC-RI). Regarding fatty acids, a total of 21 molecules were identified, with predominance of saturated fatty acids in all cupcakes samples. Individually, palmitic acid and oleic acid were detected in the highest percentages. Among free sugars, sucrose (the major form) and glucose were identified in all samples. The results demonstrate that the addition of the extract rich in rosmarinic acid caused no changes in fatty acids and sugars’ profiles, having the potential to be used in pastry products, meeting the current consumers demand.